2006
DOI: 10.1097/01.mlg.0000244389.68568.a7
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Bone Imaging in GJB2 Deafness

Abstract: Temporal bone anomalies are common in GJB2-related HL, and imaging of the temporal bone should be included in routine evaluation of these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
6
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 14 publications
(53 reference statements)
7
58
6
2
Order By: Relevance
“…2 The role of further genetic screening for mutations such as GJB6 (connexin 30) and SLC26A4 (Pendred syndrome) is not yet well defined by the literature. 3 The literature supports the use of radiologic studies in the evaluation of children with bilateral SNHL. However, which modality to use remains controversial.…”
Section: Literature Reviewmentioning
confidence: 77%
See 3 more Smart Citations
“…2 The role of further genetic screening for mutations such as GJB6 (connexin 30) and SLC26A4 (Pendred syndrome) is not yet well defined by the literature. 3 The literature supports the use of radiologic studies in the evaluation of children with bilateral SNHL. However, which modality to use remains controversial.…”
Section: Literature Reviewmentioning
confidence: 77%
“…Some suggest all children with bilateral SNHL, including those with positive GJB2 screening, should undergo imaging, whereas others suggest only children with mild-moderate SNHL or those with severe-profound SNHL and negative genetic testing should be imaged. [1][2][3][4] A few small studies have found no association between GJB2 mutations and temporal bone abnormalities. In one study, abnormalities were identified in only one of 21 GJB2-positive children, and in another study only one of 18 had an abnormality, suggesting that imaging may not be necessary if GJB2 screening is positive.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38] This topic is controversial, however, because 1 report has suggested that 72% of subjects with biallelic GJB2 mutations have at least 1 temporal bone anomaly by CT imaging, with mild endolym- phatic fossa enlargement and modiolar hypoplasia being the most common findings. 39 By far, the most common inner ear malformation seen in children with nonsyndromic hearing loss is vestibular aqueduct enlargement. The prevalence of enlarged vestibular aqueducts in children with SNHL is estimated to be 10%-15%.…”
Section: Nonsyndromic Hereditary Causes Of Hearing Lossmentioning
confidence: 99%